Hybrid Fuzzy Sliding Mode Speed Control for an Electric Vehicle Drive - Ibrahim Farouk Bouguenna; Ahmed Azaiz; Ahmed Tahour; Ahmed Larbaoui (Institute of Advanced Engineering and Science, 2017)
This paper present a speed hybrid fuzzy-sliding mode control (HFSMC) of a permanent magnet synchronous motor (PMSM) to ensure the traction of an electric vehicle; at the first we applied the sliding mode control (SMC) with three surfaces on the PMSM by taking into account the dynamics of the vehicle; And afterwards we applied the fuzzy-sliding mode in which the surface of the speed is replaced by a Fuzzy-PI controller; Simulation under Matlab/Simulink has been carried out to evaluate the efficiency and robustness of the proposed control on a system drive. It should be noted that the reference speed is the European urban driving schedule ECE-15 cycle.